2015
DOI: 10.1111/ijd.12880
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and common contact allergens in facial allergic contact dermatitis patients

Abstract: The prevalence of facial dermatitis was 27.4%. Almost half of all patients with facial dermatitis demonstrated ACD. Factors associated with facial ACD were female gender, a history of cosmetic allergy, and positive patch test reactions to hairdressing product-related allergens and preservatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
25
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 24 publications
(44 reference statements)
10
25
1
3
Order By: Relevance
“…Only epoxy resin gave significantly more positive patch test reactions in men. Other research on facial ACD and patch tests was performed in several smaller studies . In these studies, a high prevalence of contact allergy to mainly nickel, fragrances, PPD and MCI/MI was found, which corresponds to our results.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Only epoxy resin gave significantly more positive patch test reactions in men. Other research on facial ACD and patch tests was performed in several smaller studies . In these studies, a high prevalence of contact allergy to mainly nickel, fragrances, PPD and MCI/MI was found, which corresponds to our results.…”
Section: Discussionsupporting
confidence: 90%
“…Other research on facial ACD and patch tests was performed in several smaller studies. [30][31][32][33][34][35][36][37] In these studies, a high prevalence of contact allergy to mainly nickel, fragrances, PPD and MCI/MI was found, which corresponds to our results. In the study by Kasemsarn et al, the clinical relevance of positive patch test reactions was determined for each case.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, our results show that females are more prone to develop contact dermatitis. Nevertheless, a study done in Singapore during severe acute respiratory syndrome (SARS) showed no gender predisposition, but another study published in 2016 claims that females are at a higher risk of developing facial and nonfacial contact dermatitis [10,11]. Moreover, our study shows that pharmacists and medical interns have a higher chance of developing contact dermatitis.…”
Section: Discussionmentioning
confidence: 53%